Learning Enhancement of Project-Based Unit in Mechanical Engineering Undergraduate Course - Pramanik, Alokesh; Islam, N.; Basak, A.; Dong, Yu (Chandos Publishing, 2018)
Project-based learning process is nearer to the professional realism, and thus, requires lengthier period to imbibe compared to problem-based education activities. In addition, project-based learning requires application of knowledge and usually is accompanied by core subjects (e.g., maths, physics) and stronger self-direction. Therefore, students require to commit overall time management and resources. By taking consideration of above-mentioned facts, this chapter discusses the introduction of project-based manufacturing process unit which is essential for the bachelor degree course in Mechanical Engineering at Curtin University. The project was about manufacturing a hammer that cover basic manufacturing processes, such as production planning, conventional shaping and machining, computer numerical control (CNC) machining, etc. The students were required to hand-hammer drawing and step-by-step manufacturing process over the semester and discuss with the faculties in regular time interval. Finally, students’ feedbacks were recorded and analyzed. It was found that introduction of project-oriented learning improved students’ satisfaction as well as interest to learn. This change, as made in 2012, improved overall student satisfaction rate by 9% with an increasing trend.